Destruction and conservation of cultural property - Layton, Robert, 1944-; Thomas, Julian; Stone, Peter G., 1957- (London ; New York : Routledge, 2001)
Introduction: The destruction and conservation of cultural property / Robert Layton, Julian Thomas##- The uneasy bedfellows: universality and cultural heritage / Henry Cleere##- Should developing countries restore and conserve? / Patrick Mbunwe-Samba##- The end of history? Archaeology and the politics of identity in a globalized world / Bjørnar J. Olsen##- Return to Alexandria: conflict and contradiction in discourses of origins and heritage revivalism / Beverley Butler##- Renovating Hue (Vietnam): authenticating destruction, reconstructing authenticity / Mark Johnson##- Destruction and conservation of cultural property in Brazil: academic and practical challenges / Pedro Paulo A. Funari##- From museum to mantelpiece: the antiquities trade in the United Kingdom / Kathryn Walker Tubb, Neil Brodie##- A note of the excavations at Ayodhya with reference to the Mandir-Masjid issue / B.B. Lal##- The Ayodhya issue / Ram Sharan Sharma##- Ayodhya, the print media and communalism / Nandini Rao, C. Rammanohar Reddy##- The protection of Croatia's cultural heritage during war 1991-95 / Branka Šulc##- Challenges and dilemmas facing the reconstruction of war-damaged cultural heritage: the case study of Počitelj, Bosnia-Herzegovina / Sultan Barakat ... [et al.]##- Immanent or eminent domain? The contest over Thessaloniki's Rotonda / Charles Stewart##- The politics of the past: Emain Macha (Navan), Northern Ireland / Barbara Bender##- Making news out of archaeological sites: the experience at Ijaye Orile, Nigeria / C.A. Folorunso##- The changing use of worship in Roman and medieval Córdoba / John Edwards##- The Adriatic Islands Project: monument destruction and protection in the Central Dalmatian Islands / S. Čače ... [et al.]##- 'Pious vandals': restoration or destruction in Sri Lanka? / Gamini Wijesuriya##- Destruction or conservation? Some aspects of monument policy in British India (1899-1905) / Nayanjot Lahiri##- Use, value and significance in heritage manage
Includes bibliographical references (p. 311) and index.
boek